Vasorelaxant effects of ethyl cinnamate isolated from Kaempferia galanga on smooth muscles of the rat aorta - Othman, R.; Ibrahim, H.; Mohd, M.A.; Awang, Khalijah; Gilani, A.U.H.; Mustafa, Mohd Rais (2002)
From the rhizomes of Kaempferia galanga, ethyl cinnamate (EC) was isolated and its vasorelaxant effect was examined on the rat aorta. EC inhibited the tonic contractions induced by high K+ and phenylephrine (PE) in a concentration-dependent manner, with respective IC50 values of 0.30 +/- 0.05 mM and 0.38 +/- 0.04 mM. The relaxant effect against PE-induced contractions was greater in the presence of endothelium. Pre-treatment of the aorta with methylene blue and indomethacin significantly reduced the relaxant effect. These results suggest that the inhibitory effects of EC may involve inhibition of Ca2+ influx into vascular cells and release of nitric oxide (NO) and prostacyclin from the endothelial cells. Thus, the vasorelaxant effect of EC mediated through multiple pathways may explain the traditional use of the parent plant in treating hypertension.